Consequências específicas como nódulos para o estabelecimento de classes de equivalência e transferência de função - Silveira, Marcelo Vitor da (Universidade Federal de São Carlos, 2016)
This dissertation comprises four studies that aimed at the establishment of equivalence classes and transfer of functions among stimuli with common class membership with specific reinforcers. In Study 1, seven undergraduates were given to identity MTS training in which movies and tones were applied as arbitrary specific reinforcers. All participants failed on tests for the formation of equivalence classes. Thus, they were not conducted to tests for transfer of functions. Their failures were due to a redundancy of the MTS task for individuals within this population, or to the lack of defined motivational functions of the specific consequences. The nature of the consequences was manipulated in Study 2. This manipulation aimed at guaranteeing that these stimuli would act as reinforcers for six undergraduates within session behavior. The outcomes in two experiments were positive for the establishment and reorganization of equivalence classes and for transfer of functions. These results showed that the failures in Study 1 were due to the arbitrariness of the specific consequences. In Study 3, 10 undergraduates were given to a training comprised by mixed trials of arbitrary and identity MTS with specific consequences. The results on the first experiment were positive for formation and expansion of equivalence classes. Evidences for transfer of functions were also observed. However, nine of these participants had failed in tests for reorganization of the original equivalence classes. Finally, performances by seven participants confirmed that specific consequences can act as nodes for merging stimuli from separate classes. Moreover, further tests were positive for transfer of functions through stimuli within merged classes with specific consequences as nodes. The findings by these four studies for the establishment of equivalence classes and transfer of functions in procedures with different levels of complexity are showing that once class specific consequences had become class members, they will act as nodes as the antecedent stimuli (conditional and discriminative).
Specific consequences as nodes in the formation of equivalence classes and transfer of functions
Keywords: Consequências específicas; Classes de equivalência; Transferência de função; Estudantes universitários; Specific-consequences; Equivalence relations; Transfer of functions; Undergraduates; CIENCIAS HUMANAS::PSICOLOGIA